Three-dimensional anatomical characterization of the sustentaculum tali in asymptomatic adults: a computed tomography-based morphometric analysis - Xue, Runnan; Sun, Yayun; Zhu, Wenfeng (Frontiers in Surgery, 2025)
PurposeThis study aimed to establish normative anatomical references for the sustentaculum tali and talar articular surface using three-dimensional CT imaging, and to develop clinically applicable diagnostic criteria for sustentaculum tali dislocation.MethodsWe analyzed 104 normal calcanei (47 males/57 females; mean age 38.96 ± 12.97 years; 51 left/53 right feet) from January to August 2023. Three-dimensional calcaneal reconstructions were created using CT imaging data. Eight anatomical parameters were measured: sustentaculum tali dimensions (length/width/height), angular parameters (α: superior sustentaculum angle; β: inferior talar margin angle; γ: inclination angle between anterior articular surface projection and calcaneal plantar axis), and posterior talar space distance (L). Statistical comparisons were performed between genders and sides.ResultMorphometric analysis revealed the following anatomical parameters of the sustentaculum tali: length 36.93 ± 4.30 mm, width 14.65 ± 1.96 mm, and height 17.91 ± 2.34 mm. Angular measurements demonstrated α = 107.74 ± 9.59°, β = 115.34 ± 9.41°, and γ = 52.67 ± 5.98°, with posterior talar gap L measuring 4.83 ± 0.56 mm. Gender-based comparisons showed statistically significant differences in three-dimensional sustentaculum tali morphology (length/width/height) and posterior space L (all P < 0.001), with female measurements being consistently smaller than males. No significant inter-gender differences were observed in angular parameters (α/β/γ, P > 0.0). Laterality analysis revealed no statistically meaningful variations between left and right feet across all measured parameters.ConclusionThis study establishes normative 3D-CT anatomical parameters of the sustentaculum tali in healthy individuals (n = 104), revealing significant gender-based differences in dimensions and posterior talar gap distance L (all P < 0.001). Critical gender-specific diagnostic thresholds for dislocation were defined: L > 7.25 mm (males) and >6.49 mm (females). Combined with screw trajectory angles (α/β/γ) and sustentaculum dimensions (length/width/height), these data provide an evidence-based framework for preoperative planning, urgent reduction indication, and precision screw placement in calcaneal fracture management.